Characterization of Natural Cellulose Fiber from the Barks of Vachellia farnesiana. Issue 4 (3rd April 2022) - Vijay, R.; James Dhilip, Jafrey Daniel; Gowtham, S.; Harikrishnan, S.; Chandru, B.; Amarnath, M.; Khan, Anish
ABSTRACT: The need for environmental friendly materials have stimulated researchers to carry out works in natural fibers, which are substitute for human-made synthetic fibers in many lightweight medium load applications. In the present work, Vachellia farnesiana fiber was selected as a natural fiber. The obtained Vachellia farnesiana fibers were characterized for physical and chemical properties, Thermo Gravimetric Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and, tensile strength. Scanning Electron Microscope (SEM) was used to capture its morphological characteristics. The outcome of the chemical analysis showed the weight percentage of ɑ-cellulose, hemicellulose, moisture content, wax, density and the same was confirmed by the output of the FTIR test. XRD test results showed that Vachellia farnesiana fiber had a crystallinity index of 13% and a crystal size of 31.89 nm. Thermal analysis showed a char residue of 28.71%.